The Impact Of Reconstruction Filters On 99mtc Myocardial Spect Imaging - Yusoff, Muhammad Nur Salihin (2010)
This prospective and retrospective study was undertaken to investigate the effect of filtering on image quality and functional parameters in myocardial SPECT using various reconstruction filters and their associated parameters. In the image quality study (a prospective study), a cardiac phantom system (with 1.10 cm cold defect in myocardium) for different 99mTc radioactivity concentration as background was used in the SPECT procedure. The target-background concentration ratio (T/B) of 5.3, 4.0, 3.3, 2.7, 2.0, 1.3, and 1.0 were used to acquire SPECT images. Based on the SPECT studies, the calculated background count to target count ratio (BTR) for each T/B was 0.2, 0.4, 0.6, 0.7, 0.8, and 0.9 respectively (T/B = 1.0 was excluded). The image quality was analyzed based on image contrast, signal-to-noise ratio (SNR), defect size accuracy, and total grade (trade-off between contrast, SNR, and defect size accuracy). The results showed that, different filters produce different values of contrast, SNR, and defect size. The increase in cut off frequency and order of filter resulted in the increase in contrast and SNR, but the accuracy of defect size was reduced. Butterworth filter has the ability to balance between contrast, SNR, and defect size accuracy while Gaussian filter is good in producing image with high contrast and SNR.